Stem cell, Granulocyte-Colony Stimulating Factor and/or Dihexa to promote limb function recovery in a rat sciatic nerve damage-repair model: Experimental animal studies. (November 2021) - Weiss, Jessica B.; Phillips, Cody J.; Malin, Edward W.; Gorantla, Vijay S.; Harding, Joseph W.; Salgar, Shashikumar K.
Abstract: Background: Optimizing nerve regeneration and re-innervation of target muscle/s is the key for improved functional recovery following peripheral nerve damage. We investigated whether administration of mesenchymal stem cell (MSC), Granulocyte-Colony Stimulating Factor (G-CSF) and/or Dihexa can improve recovery of limb function following peripheral nerve damage in rat sciatic nerve transection-repair model. Materials and methods: There were 10 experimental groups (n = 6–8 rats/group). Bone marrow derived syngeneic MSCs (2 × 10 6 ; passage≤6), G-CSF (200–400 μg/kg b.wt.), Dihexa (2–4 mg/kg b.wt.) and/or Vehicle were administered to male Lewis rats locally via hydrogel at the site of nerve repair, systemically (i.v./i.p), and/or to gastrocnemius muscle. The limb sensory and motor functions were assessed at 1–2 week intervals post nerve repair until the study endpoint (16 weeks). Results: The sensory function in all nerve boundaries (peroneal, tibial, sural) returned to nearly normal by 8 weeks (Grade 2.7 on a scale of Grade 0–3 [0 = No function; 3 = Normal function]) in all groups combined. The peroneal nerve function recovered quickly with return of function at one week (∼2.0) while sural nerve function recovered rather slowly at four weeks (∼1.0). Motor function at 8–16 weeks post-nerve repair as determined by walking foot print grades significantly (P < 0.05) improved with MSC + G-CSF or MSC + Dihexa administrations into gastrocnemius muscle and mitigated foot flexion contractures. Conclusions: These findings demonstrate MSC, G-CSF and Dihexa are promising candidates for adjunct therapies to promote limb functional recovery after surgical nerve repair, and have implications in peripheral nerve injury and limb transplantation. IACUC No.215064. Highlights: G-CSF in combination with MSCs improved limb function recovery in sciatic nerve transection- repair model. Dihexa in combination with MSC improved limb function recovery in sciatic nerve transection- repair model. Foot flexion contractures were reduced with G-CSF & MSC or Dihexa & MSC administration into target muscle gastrocnemius. MSC, G-CSF or Dihexa combination therapy is attractive, feasible & promising in peripheral nerve injury repair and have implications in limb transplantation. The findings warrant further investigation to understand the cellular/molecular mechanisms.